Grid Integration of Solar and Solar/Wind Hybrid Mini-Grid Projects: A Case of Solar/Wind Hybrid Mini-Grid Project Implemented by AEPC - Bhandari, Khem Raj; Adhikari, Narayan Prasad (Journal of the Institute of Engineering, 2020)
Alternative Energy Promotion Center (AEPC) has been scaling up renewable energy technologies through Mini-grid power supply in Nepal’s off-grid areas in order to fulfill community electricity demands for both households and electricity-based enterprises. It is likely that, in some of the off-grid renewable energy (RE) mini-grid service areas, Nepal Electricity Authority (NEA) grid line might reach in near future. The objective of this study is to highlight success stories of solar and solar/wind mini-grids implemented by AEPC and for their longer-term sustainable operation grid integration policy of isolated mini-grid systems will require. Till the date AEPC has successfully electrified more than 20 rural communities through solar and solar/wind hybrid mini-grid systems. Some of these isolated mini-grid projects will seek grid interconnections in near future due to NEA distribution system expansion trend. When the isolated mini-grids will be connected to the national grid power network in future, the mini-grid can feed surplus electricity to the local utility grid line and will receive deficit electricity from the local utility grid system to serve the consumers connected to the local grid network. The methodology applied to this study is assessment of existing solar and solar/wind mini-grid projects, technological intervention required for grid integration, reviewing grid-connection policy of distributed renewable generations in the country and recommendation of relevant policy option for grid connection of rural mini-grids. Grid integration of isolated solar and solar/wind mini-grids will have positive impacts to the sustainability of the present isolated mini-grids, will help in retaining existing mini-grids end users, energy produced by mini-grid systems will be optimally utilized, the existing mini-grid power will contribute to stabilize weak national grid electrical parameters. The outcome of the study will recommend need of policy options as well as technological interventions in order to do grid integration of solar and solar/wind hybrid mini-grid systems in Nepal.